Is demography destiny? Urban population change and economic vitality of future cities - Jacques Poot; Shefali Pawar (Journal of Urban Management, 2013)
The growth of cities has attracted considerable scholarly attention during the last decade as it is becoming clear that powerful agglomeration forces are reinforcing the role of cities as the engines of economic growth. Close to 4 billion people live in cities, about 55 per cent of the world's population. While population growth rates are declining and the world's population is likely to level off from the middle of the 21st century, probably ending up around 10 billion, further urbanization is expected to continue. Another 3 billion people will become urban citizens this century. At the same time no corner of the world will be sheltered from sweeping demographic changes due to population ageing and increasing migration. Such changes will be amplified in cities. In this paper we combine UN population projections and migration data with our own assumptions to derive projections of age composition and birthplace composition of urban populations by continent. We also briefly address the consequences of these demographic trends for future urban economic vitality. Particular attention is paid to the impacts of demographic changes on urban creativity and innovation. We conclude that, with the right policies in place, such demographic changes enhance rather than impede the future prosperity of the urban world.
Keywords: 710; ageing; ethnic diversity; migration; urbanization; World population projections